Report on professional attachment with company XYZ. - Chan, Guat Hong. (2008)
At Training & Organisational Effectiveness (T&OE), author conduct an internal customer service survey to determine the level of internal customer service, after which, to design a customer service training program that addresses the areas where weak customer service is revealed in the survey.